Trauma and the rehabilitation of trafficked women: the experiences of Yazidi survivors - Hosseini, S. Behnaz (Routledge research in gender and society, 2020)
"Based on research in camps in Iraqi Kurdistan and among refugees in Germany, this book addresses the challenges, strategies and support systems that exist for the rehabilitation and reintegration of Yazidi women recovering from human trafficking. Through in-depth interviews, focus group discussions and case studies, it gives women trafficked by ISIS their own voice to express their experiences during captivity, whilst offering an overview of the forms of support and protection available and necessary for survivors. An examination of the experiences and needs of refugee women who have undergone traumatizing experiences, Trauma and the Rehabilitation of Trafficked Women will appeal to scholars and policy makers with interests in gender studies, feminist thought, sexual violence during war, human trafficking and trauma recovery"--